Outcomes of Nonsevere Relapses in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis Treated With Glucocorticoids. Issue 6 (June 2015) - Miloslavsky, E. M.; Specks, U.; Merkel, P. A.; Seo, P.; Spiera, R.; Langford, C. A.; Hoffman, G. S.; Kallenberg, C. G. M.; St.Clair, E. W.; Tchao, N. K.; Ding, L.; Iklé, D.; et al.
<x xml:space="preserve">Abstract</x> Objective Nonsevere relapses are more common than severe relapses in antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV), but their clinical course and treatment outcomes remain largely unexamined. We undertook this study to analyze the outcomes of patients with nonsevere relapses in the Rituximab in ANCA‐Associated Vasculitis (RAVE) trial who were treated with prednisone according to a prespecified protocol. Methods RAVE was a randomized, double‐blind, placebo‐controlled trial comparing rituximab (RTX) to cyclophosphamide (CYC) followed by azathioprine (AZA) for induction of remission. Patients who experienced nonsevere relapses between months 1 and 18 were treated with a prednisone increase without a concomitant change in their nonglucocorticoid immunosuppressants, followed by a taper. Results Forty‐four patients with a first nonsevere relapse were analyzed. In comparison to the 71 patients who maintained relapse‐free remission over 18 months, these patients were more likely to have proteinase 3–ANCAs, diagnoses of granulomatosis with polyangiitis (Wegener's), and a history of relapsing disease at baseline. A prednisone increase led to remission in 35 patients (80%). However, only 13 patients (30%) were able to maintain second remissions through the followup period (mean 12.5 months); 31 patients (70%) had a second disease relapse, 14 of them with severe disease. The mean time to second relapse was 9.4 months (4.7 months in the group treated with RTX versus 13.7 months in the group treated with CYC/AZA; P < 0.01). Patients who experienced nonsevere relapses received more glucocorticoids than those who maintained remission (6.7 grams versus 3.8 grams; P < 0.01). Conclusion Treatment of nonsevere relapses in AAV with an increase in glucocorticoids is effective in restoring temporary remission in the majority of patients, but recurrent relapses within a relatively short interval remain common. Alternative treatment approaches are needed for this important subset of patients.